Arab Republic of Egypt - Integrated Irrigation Improvement and Management Project and Farm-Level Irrigation Modernization Project : Project Performance Assessment Report - World Bank (Washington, DC, 2022)
Ratings for the Integrated Irrigation Improvement and Management Project are as follows: Outcome was moderately satisfactory, Risk to development outcome was modest, Bank performance was moderately satisfactory, and Borrow performance was moderately satisfactory. Ratings for the Farm-Level Irrigation Modernization Project are as follows: Outcome was moderately satisfactory, Risk to development outcome was modest, and Bank performance was moderately satisfactory. This assessment offers the following lessons: (i) In irrigation systems, such as the Nile Delta’s, that are organized along a hierarchical canal network, irrigation improvement efforts can realize greater impact by applying a systematic approach to rehabilitation, as was done through these two projects, as opposed to addressing different levels of the canal system in isolation. (ii) Efficient implementation of irrigation improvement works requires coordinating and sequencing activities that fall under the mandate of many different entities, which are often beyond the authority of the project implementing agency. (iii) Effecting behavior changes in on-farm water use, agronomic practices, and diversification to higher-value crops requires support beyond improvements to the irrigation water delivery system. (iv) Successfully reforming the institutions that manage irrigation and drainage services, both water users and government agencies, requires greater attention to incentives for collaboration. (v) In a context such as the Nile Delta, where overall efficiency of the irrigation system is already high, there is little scope for addressing water savings at the basin level through infrastructure improvement.